(untitled) (The Pakistan Development Review, 2010)
A standard labour contract has two important components, agreed upon wage from principal and efforts that in return is provided by agent. On one hand both principal and agent have full knowledge of wage, while information on provided effort level is always incomplete due to its abstract nature. Principal can only observe output of agent, which is joint function of effort, skill level and work environment [Green (1992)]. Assuming economic agents strictly follow their material gain, the game theoretic model predicts that agent will utilise minimum possible effort level. Similarly, the principal will pay minimum wages, since additional wages cannot extract additional effort. In contrast, the gift exchange model (GEM) is based on the critical assumption that reciprocal behaviour creates a positive relationship between wages and workers‘ effort levels [Akerlof (1982, 1984)]. Workers are assumed to reciprocate higher wage levels from firms by increasing their effort (positive reciprocity) and /or by decreasing their effort in retaliation for low wage (negative reciprocity). In labour market as partial gift exchange, the loyalty of workers is exchanged for higher wage, and this loyalty then can be translated to higher productivity through effective management. Experimental evidence has supported the reciprocity hypothesis both in laboratory [Fehr and Falk (2008); Fehr, et al. (1993); Fehr and Tougareva (1995); Fehr and Falk (1999); Fehr, et al. (1998); Fehr, Gächter, and Kirchsteiger (1997)] and in the field [Falk (2007); Henning- Schmidt, et al. (2005); Bellemare and Shearer (2007)].